State industry of the USSR at the stage of its restoration - Inna G. Onoprienko, Marina A. Sergienko, Elena Yu. Prokofieva,; Svetlana B. Shatohina, Vladimir S. Kulabuhov, (Opción, 2019)
The authors of the paper propose to consider the features of the state industry development in the USSR at the stage of restoration in the mid-1920s via logical, comparative-historical, and problem-chronological methods. As a result, the general development of local industry, in comparison with the territory and number of people in national republics, is completely insignificant, and is an urgent task. The team of authors comes to the conclusion that during this period the industry was given the task of creating a united industrially developed national economic complex in the USSR.